2021
DOI: 10.3390/polym13020198
|View full text |Cite
|
Sign up to set email alerts
|

New Concept in Bioderived Composites: Biochar as Toughening Agent for Improving Performances and Durability of Agave-Based Epoxy Biocomposites

Abstract: Biocomposites are increasingly used in the industry for the replacement of synthetic materials, thanks to their good mechanical properties, being lightweight, and having low cost. Unfortunately, in several potential fields of structural application their static strength and fatigue life are not high enough. For this reason, several chemical treatments on the fibers have been proposed in literature, although still without fully satisfactory results. To overcome this drawback, in this study we present a procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
(76 reference statements)
3
8
0
Order By: Relevance
“…The matrix used for both biocomposites considered was a green epoxy produced by the American Entropy Resin Inc. (San Antonio, CA, USA), named SUPERSAP CNR, with IHN-type hardener [ 28 ]. As widely shown in previous studies [ 24 , 25 , 26 , 27 ] by the same authors, this matrix exhibits an almost linear elastic behavior with density ρ m = 1.05 g/cm 3 , tensile strength σ m , R 50 MPa, Young modulus E m ≅ 2.7 GPa, and tensile fracture strain ε m , R ≅ 2.5% (see also Table 1 ).…”
Section: Materials and Manufacture Of Biocompositessupporting
confidence: 80%
See 1 more Smart Citation
“…The matrix used for both biocomposites considered was a green epoxy produced by the American Entropy Resin Inc. (San Antonio, CA, USA), named SUPERSAP CNR, with IHN-type hardener [ 28 ]. As widely shown in previous studies [ 24 , 25 , 26 , 27 ] by the same authors, this matrix exhibits an almost linear elastic behavior with density ρ m = 1.05 g/cm 3 , tensile strength σ m , R 50 MPa, Young modulus E m ≅ 2.7 GPa, and tensile fracture strain ε m , R ≅ 2.5% (see also Table 1 ).…”
Section: Materials and Manufacture Of Biocompositessupporting
confidence: 80%
“…In detail, the sisal fabrics, that are not disposable in the current market, were obtained by manual stretching of the fibers in order to eliminate natural undulations; alignment of the straight fibers arranged into small groups, the transversal stitching by using an automatic machine (see Figure 1 b). These unidirectional fabrics, also used to manufacture the pure sisal cross-ply biocomposites (SFRP) considered to compare the performance of the B-FSRP, were the same as those already used in several previous studies by the same authors [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Materials and Manufacture Of Biocompositesmentioning
confidence: 99%
“…Zuccarello et al [127] reported an increase of ultimate tensile stress and strain by about 55% and 250%, respectively, by adding 2 wt.% BC obtained from Mischantus pyrolyzed at 550 • C to agave epoxy composites. Nonetheless, the greatest improvements were achieved considering the specific failure energy fatigue life performance that became 5 times and 3 orders of magnitude bigger with respect to the composites without BC.…”
Section: Other Thermoplastic-based Compositesmentioning
confidence: 99%
“…A noticeable improvement in mechanical properties has been obtained by introducing a suitable concentration of biochar particles in eco-friendly bio-composites manufactured by a green epoxy matrix reinforced with short agave fibers for replacing synthetic materials in structural applications [ 83 ]. In that case, with the optimum amount of BC particles (in this case found to be equal to 2 wt.%) added by means of the synergic effect of short fiber and biochar particles, a better adhesion has been achieved between the epoxy matrix and fiber, which was demonstrated by the fiber pull-out test.…”
Section: Bio-polymer-based Composites Containing Bcpmentioning
confidence: 99%